Water towers in Lima. State of utilitarian heritage of the 20th century - Leandro Flores, Israel (2015)
The city generates landmarks or monuments only if it is able of inventing or recognize them. Either way, the valoration of an asset or an artifact goes in hand with the assumption as a human being and as a collective. Society as such requires to recognize through itself and its reality, in other words, its physical context and mental context. As a self-assertion. Knowing its heritage is a plain exercise of self-esteem and collective reason. But, what happen when society doesn´t know what assets they have? Can we talk about an unrecognized heritage? Or maybe a diminished heritage? This work pretends to make a statement about the conditions that must comply the testimony of the city’s growth, as are the Water Towers in Lima, and as the Water Towers in Lima and the reasons of its acceptance as collective memory and valorative reason.